PENGARUH METODE PENGAKUAN PENDAPATAN TERHADAP LABA PERUSAHAAN PT. TEBING TONDONG JAYA - Shelly Carolina (Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The purpose of this study is to find the relationship between marketing mix and communication towards customer loyalty. The marketing mix and communication have a close relationship to increase customer loyalty. If the marketing mix and communication is done well, it will give satisfaction to the customer so that the customer will continue to use the company's products in the future. The research methodology that is being used to measure is by survey, the type of research is quantitative descriptive and the nature of this research is explanatory research. The populations in this research were customers of PT. Bank Maspion Indonesia, Tbk Medan Branch as many as 163 people with a sample of 116 people. The method of data collections are done by distributing questionnaires, interviews, and literature studies. The variable was measured by a Likert scale. The data analysis model that has been used to answer the hypothesis is multiple regression. The results showed that marketing mix and communication simultaneously have a significant affect on customer loyalty at PT. Bank Maspion Indonesia, Tbk Medan Branch. Partially, the marketing mix does not have a significant affect on customer loyalty at PT. Bank Maspion Indonesia, Tbk Medan Branch and communication has a significant affect on customer loyalty at PT. Bank Maspion Indonesia, Tbk Medan Branch